Diseño de un plan de Importación de volquetas eléctricas Lk2000 para la industria minera del municipio de Almaguer Cauca desde la República Popular de China. (2022)
By means of the investigation, an import process is carried out to verify the viability of the same, demonstrating the ease at the time of commercializing this type of products to the Colombian market, by means of an import plan the whole step by step of the process was evaluated, which is very favorable for the merchants since its requirements in the documentary part are not as complex as it is imagined, You must be registered with the Communications Regulation Commission (CRC) and the National Tax and Customs Directorate (DIAN) to be recognized as an importer before the Colombian authorities, and also to be able to access the Customs quotations.